2010
DOI: 10.1016/j.ijgo.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Implications of cycle length immediately after discontinuation of combined oral contraceptives on use of the Standard Days Method

Abstract: A first post-COC cycle within the 26-32-day range did not predict a second cycle within range. Women discontinuing COC should not start using the SDM in their first or second post-COC cycle, even if the first cycle falls within the stated range. Instead, they should use a backup method until they meet the necessary eligibility criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The return of the first spontaneous menstrual bleed, which is an indicator of the return of normal ovarian function, appeared in 80.9% of the women within 35 days after the COC-induced withdrawal bleed. However, only 67.6% of the women regained three regular menstrual bleeds during the follow-up, indicating some irregularity within the first 3 months after COC discontinuation, as also previously reported (Arévalo et al, 2010;Duijkers et al, 2005). Women using the contraceptive pill express much concern about their fertility after discontinuation of COC use (Landersoe et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
“…The return of the first spontaneous menstrual bleed, which is an indicator of the return of normal ovarian function, appeared in 80.9% of the women within 35 days after the COC-induced withdrawal bleed. However, only 67.6% of the women regained three regular menstrual bleeds during the follow-up, indicating some irregularity within the first 3 months after COC discontinuation, as also previously reported (Arévalo et al, 2010;Duijkers et al, 2005). Women using the contraceptive pill express much concern about their fertility after discontinuation of COC use (Landersoe et al, 2019).…”
Section: Discussionsupporting
confidence: 52%
“…In most studies, SDM was offered as part of the standard FP and reproductive health (RH) service delivery in the study site catchment area: In 10 studies, SDM was offered alone, and in other studies it was compared to condoms, injectables, sterilization, Depo-Provera (DMPA), and pills (Arévalo et al 2010b;Dosajh, Ghosh and Lundgren 2006;Gribble et al 2008;Johri, Panwar and Lundgren 2005;Kavle, Eber and Lundgren 2012;León et al 2006;León et al 2007a;Lundgren et al 2005;Mohammadpourasl 2007;Ram and Doracaj N.D.;Rosen, Winfrey and Adesina 2013). The typical population in SDM studies comprised women of reproductive age who use SDM; some studies included comparisons of SDM users to non-users.…”
Section: Figure 1 Sdm Studies In India Bymentioning
confidence: 99%
“…A study using retrospective data in Brazil that examined the potential for SDM use following discontinuation of combined oral contraceptives (COCs) showed that 53 percent of women discontinuing COCs had out-of-range cycles compared to 27 percent in the control group (Arévalo et al 2010b), suggesting that SDM may not be an appropriate method immediately following discontinuation of hormonal methods, and that potential users should have three consecutive cycles within the 26 to 32 day range for eligibility criteria (Arévalo et al 2010b). (Arévalo et al, 2010a;Arévalo, Jennings & Sinai, 2002;IRH, 2008;Kalaca et al, 2005; Knowledge of SDM and other Contraceptive Methods…”
Section: Experience With Out-of-range Cyclesmentioning
confidence: 99%